IMPROVING PUBLIC SERVICE QUALITY THROUGH THE IMPLEMENTATION OF GOOD GOVERNANCE AT THE SURABAYA CITY REVENUE AGENCY - Purdiono, Andri; Pramudiana, Ika Devy; Haryati, Eny; Pramono, Sapto (DIA: Jurnal Administrasi Publik, 2026)
This study is motivated by the importance of public service in realizing good governance. However, public service quality often remains challenging when implementing good governance principles. Therefore, this study aims to evaluate the application of five main principles of good governance—transparency, accountability, participation, responsiveness, and efficiency—to improve the quality of public services at the Surabaya City Revenue Agency. This study uses a qualitative method with a descriptive approach to identify and evaluate the success indicators of these five principles as applied in the agency. Data were collected through observation, interviews, and document analysis related to public services at the Surabaya City Revenue Agency. Results show that transparency in public services has reached 76%, indicating openness of information, though accessibility and completeness of data still need improvement. Accountability stands at 73%, highlighting a need for enhancement in accountability procedures. Community participation is recorded at 68%, indicating the need for increased accessibility and opportunities for public involvement. Responsiveness reaches 70%, which, while adequate, still requires improvements in responsiveness to public needs. Efficiency is at 72%, requiring simplifying procedures to accelerate service delivery. This study concludes that the application of good governance principles at the Surabaya City Revenue Agency is relatively well-implemented but requires improvements in several areas. To enhance public service quality, this study recommends developing an integrated online information system to support transparency, conducting public consultation programs and periodic satisfaction surveys to boost participation, and simplifying administrative procedures alongside digitalizing services to increase efficiency. By implementing these recommendations, it is hoped that the Surabaya City Revenue Agency can become more responsive, transparent, and efficient in serving the public, ultimately enhancing public trust in public services and achieving the goals of good governance optimally.